PENGARUH MOTIVASI, KOMUNIKASI, LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT. BPR PUSAKA DENPASAR - Ni Made Indah Satya Dewi; Ida Bagus Made Widiadnya; Putu Pradiva Putra Salain (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Human resources are the main factor in organizational development. Human resources in the company are allpeople involved in organizational development, especially employees. An organization/institution requires a competentand creative employee to achieve organizational goals. Employees have an important role in an organization, namely as thinkers, planners and controllers of organizational activities. This study aims to examine and analyze the influence of motivation, communication, physical work environment on employee performance at PT. BPR Pusaka Denpasar totaling 37 people. Samples were taken using saturated samplingmethod. Data analysis using multiple linear regression. The results of this study indicate that motivation has a positive and significant effect on employee performanceat PT. BPR Pusaka Denpasar. Communication has a positive and significant effect on employee performance at PT. BPR Pusaka Denpasar. The physical work environment has a positive and significant effect on employee performance at PT.BPR Pusaka Denpasar.